Online file sharing : innovations in media consumption - Schwarz, Jonas Andersson (New York : Routledge, 2014)
"It is apparent that file sharing on the Internet has become an emerging norm of media consumption especially among young people. This book provides a critical perspective on this phenomenon, exploring issues related to file sharing, downloading, peer-to-peer networks, "piracy," and (not least) policy issues regarding these practices. Andersson Schwartz critically engages with the justificatory discourses of the actual file-sharers, taking Sweden as a geographic focus. By focusing on the example of Sweden home to both The Pirate Bay and Spotify he provides a unique insight into a mentality that drives both innovation and deviance and accommodates sharing in both its unadulterated and its compliant, business-friendly forms"--
Includes bibliographical references and index.
Keywords: Peer-to-peer architecture -- Social aspects; Computer file sharing -- Technological innovations; Social media; SOCIAL SCIENCE / Media Studies; COMPUTERS / Social Aspects / General; COMPUTERS / Internet / Security